The National University of Costa Rica Program Profiles, Dynamics and Challenges of the Costa Rican Education: A Proposal for Pedagogical Innovation and the Production of Materials and Technological Didactic Resources - Luis Alfredo Miranda-Calderón; Ligia María Angulo-Hernández; Guiselle Román-López (Universidad Nacional, Costa Rica, 2017)
Profiles, Dynamics and Challenges of the Costa Rican Education is a program planned to be executed in a five-year period: 2014-2018. It is being executed within the framework of processes of research, teaching, university extension, and production of the Center for Research and Teaching in Education (CIDE in Spanish) of the National University of Costa Rica. This proposal considers the implementation of two sub-programs approaching two important areas: pedagogical innovation, and the production of materials and didactic technological resources. The first sub-program, Innovation, is oriented to highlighting and valuing the set of practices and successful experiences in the field of teaching, and assuming processes associated to it, such as the professional practice activities and the graduation final work proposals in different modalities. The second sub-program, Production of Didactic Technological Resources, supports the development of projects through consulting, design, and production of materials and didactic technological resources. This paper describes the methodological route proposed for the Production sub-program, along with some of the preliminary results achieved at the beginning of the implementation of the proposal. Finally, the article presents a series of reflections about the diverse dimensions that the program covers, its scope, impact, challenges, and constraints that must be assumed, as well as the different contributions in the four substantive areas on which the National University of Costa Rica bases its work: teaching, research, university extension and production.